THEORETICAL AND EXPERIMENTAL STUDY OF THE HYDRAULIC JUMP IN U-SHAPED CHANNEL WITH POSITIVE SLOPE - CHERHABIL, S; DEBABECHE, M (Courrier du Savoir; Vol. 21 (2016): COURRIER DU SAVOIR (NOVEMBRE), 2016)
This paper presents both theoretical and experimental study of the hydraulic jump in a sloped U–shaped channel. A theoretical relation expressing the inflow Froude number as function of the upstream and downstream relative heights, the relative length of the jump and the channel slope. An experimental analysis is also proposed in order to correct the proposed relationship. For this purpose, six positive slopes are tested.